2016
DOI: 10.1016/j.nefro.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic kidney disease: Is there a non-albuminuric phenotype in type 2 diabetic patients?

Abstract: The majority of patients with DKD had albuminuria, but a significant proportion had a non-albuminuric phenotype (46.6% in this population). These patients exhibit distinct clinical features that could have screening, therapeutic and prognosis implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
1
18
0
2
Order By: Relevance
“…We also found that albuminuria was absent in 31.8% of subjects with CKD stages 3 to 5 (eGFR < 60 ml/min/1.73m 2 ). In line with this a recent study found that approximately one half (46.6%) of diabetics with CKD had reduced eGFR without albuminuria [33]. Inadequacies of CKD diagnosis in diabetes from routine clinical assessment also are mentioned frequently in the literature [11,12,31], indicating the need for a simple functional measurement of GFR, as provided using the eGFR.…”
Section: Discussionmentioning
confidence: 73%
“…We also found that albuminuria was absent in 31.8% of subjects with CKD stages 3 to 5 (eGFR < 60 ml/min/1.73m 2 ). In line with this a recent study found that approximately one half (46.6%) of diabetics with CKD had reduced eGFR without albuminuria [33]. Inadequacies of CKD diagnosis in diabetes from routine clinical assessment also are mentioned frequently in the literature [11,12,31], indicating the need for a simple functional measurement of GFR, as provided using the eGFR.…”
Section: Discussionmentioning
confidence: 73%
“…En cambio, la etiología de la ERD-NA en diabéticos tipo 2 podría ser más variable. Desafortunadamente, aunque la ERD-NA en diabéticos tipo 2 ha sido descrita en una gran variedad de estudios, en ellos se hace diferenciación respecto a características clínicas y hábitos entre su condición normoalbuminúrica vs. microalbuminuria o macroalbuminuria, sin recurrir a la biopsia renal para obtener un diagnostico definitivo [2][3][4][5][6][7] .…”
Section: Discussionunclassified
“…La prevalencia de esta enfermedad [2][3][4] varía entre 25 % a 50 % de los pacientes que exhiben TFG menor a 60 ml/min/1,73mt2. Los pacientes con ERD-NA presentan características diferentes a la población albuminúrica, tales como: mayor proporción de sexo femenino, edad mayor, menor TFG, buen control de la presión arterial, raza blanca no hispanos, menor prevalencia de tabaquismo y mayor prevalencia de polineuropatía [5][6][7] .…”
Section: Introductionunclassified
“…The reported prevalence of DN varies widely worldwide. It is generally thought that the clinical onset of DN is characterized by the presence of micro-albuminuria or reduction in estimated glomerular filtration rate (eGFR) (Kramer et al, 2003;Pavkov et al, 2012;Shimizu et al, 2014;Laranjinha et al, 2016;Cameron, 2016). However, an autopsy study recently found the absence of micro-albuminuria in some patients with biopsy-proven DN (Klessens et al, 2016), which reminds us that a relative part of DN was clinically under-diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Other studies of renal biopsy in DM have documented that non-diabetic renal disease (NDRD) plays a significant role in diabetic patients. The reported proportion of NDRD alone ranges from 18.1%-82.9% (Pavkov et al, 2012;Byun et al, 2013;Sharma et al, 2013;Zhuo et al, 2013;Horvatic et al, 2014;Zwi et al, 2014;Klessens et al, 2016;Laranjinha et al, 2016;Liu, Tian & Jian, 2016) in diabetic patients with renal disease, while that of NDRD superimposed on DN ranges from 7.8%-48.9% (Oh et al, 2012;Pavkov et al, 2012;Byun et al, 2013;Zhuo et al, 2013;Horvatic et al, 2014;Zwi et al, 2014;Klessens et al, 2016;Laranjinha et al, 2016;Liu, Tian & Jian, 2016). It is suggested that the absence of histopathologic evaluation may lead to a relatively high proportion of NDRD that were misdiagnosed as DN among diabetic patients.…”
Section: Introductionmentioning
confidence: 99%